Cryogenic Micropunching of Polymeric Films for Tissue Engineering Applications. - Sagar, Amrit. (2017)
Abstract: Three dimensional synthetic tissue scaffolds with simulated micro-vascularity can be produced by multilayer stacking of 2D porous membranes. In order to make 2D porous membranes, cryogenic micropunching of thin Polycaprolactone (PCL) films was investigated experimentally and through finite element simulation using DEFORM 3D. Material properties of PCL, below its glass transition temperature, were determined experimentally through uniaxial compression testing of samples immersed in liquid nitrogen. Micropunching experiments were carried out for two film thicknesses, 40 μm and 70 μm. Three different die clearances were considered for each film thickness: 15%, 30%, and 45% clearance for 40 μm thick films, and 8.6 %, 17.1 %, and 25.7 % clearance for 70 μm thick films. For each experiment, the peak punching force was measured for a nominal hole diameter of 200 μm. Experimentally determined material properties of PCL were used in the finite element simulation to predict peak punching forces for comparison to experiments. The predicted peak punching forces matched the measured forces with best case error of 2% and worst case error of 31 %. Maximum achievable porosity was also investigated experimentally and through simulation by punching one hole close to a pre-existing hole and reducing the minimum web thickness between holes gradually by steps of approximately 10 µm in 70 μm thick PCL films. The maximum achievable porosity was determined to be approximately 75% for 200 μm diameter holes arranged in a hexagonally close packed pattern in 70 μm thick PCL film. Apart from PCL, thin copper foils were punched and peak punching force was measured and compared with the numerical results to study the predictive capability of conventional finite element simulation when feature dimensions are comparable in size to material grains. It was concluded that Crystal Plasticity Finite Element simulations are not necessary for predicting the peak punching force while micropunching copper foil for the range of die clearances considered in the current research. Finally, a new analytical model was developed to study the effect of slanted punches on the punching force and verified by finite element analysis. An association between the instantaneous rate of shear area propagation and the punching force profile was predicted analytically and confirmed by finite element simulation.; Thesis (Ph.D.)--Tufts University, 2014.; Submitted to the Dept. of Mechanical Engineering.; Advisor: Thomas James.; Committee: Thomas James, Anil Saigal, Robert White, Stuart Brown, and Li Zeng.; Keyword: Mechanical engineering.